Politics of Islamic Education During the Old Order - Faisal Caniago; Sehat Sultoni Dalimunthe (Formosa Journal of Sustainable Research, 2023)
This paper explains how the politics of Islamic education occurred during the Old Order. Presented how the development of Islamic education in Indonesia. Government policies specifically in the implementation of Islamic education tend to change from time to time, both related to a number of religious education policies in schools, religious education policies in madrasas, and also in Islamic tertiary institutions